SceneSync - A Hypermedia Authoring Language for Temporal Synchronism of Learning Objects - Busson, Antonio José G.; Damasceno, André Luiz de B.; Lima, Thacyla de Sousa; Neto, Carlos de Salles Soares (Proceedings of the Brazilian Symposium on Multimedia and the Web (WebMedia); 2016: Proceedings of the 22nd Brazilian Symposium on Multimedia and the Web, 2016)
Learning Objects (LOs) are entities, digital or not, that can be used, reused or referenced during the teaching process. According to Multimedia Systems area, they are specified by documents that establish several spatiotemporal synchronization relationships of their contents. LOs allow students to individualize the learning experience with non-linear navigation mechanisms and content adaptation. The paper presents a survey of requirements for the set of documents representing such LOs as well as desirable aspects for expressing during authoring phase. In addition, this paper presents a multimedia conceptual model that answers such requirements gathered. The model is implemented by SceneSync, a domain specific language focused on the temporal synchronism of LOs. As a result of the work, it is presented the SceneSync modeling of a nonlinear LO illustrating all initially identified requirements, attesting the expressiveness and applicability of the language.